2005
DOI: 10.1111/j.1432-2277.2005.00185.x
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Kupffer cell modulation with glycine versus Kupffer cell depletion after liver transplantation in the rat: effects on postischemic reperfusion injury, apoptotic cell death graft regeneration and survival*

Abstract: Summary Inhibition or destruction of Kupffer cells (KC) may protect against ischemia‐reperfusion (IR) induced primary graft nonfunction (PNF) in liver transplantation. Besides KC activation, PNF is characterized by microvascular perfusion failure, intrahepatic leukocyte accumulation, cell death and hepatocellular dysfunction. KCs can be inactivated by different agents including gadolinium chloride (GdCl3), methyl palmitate (MP) and glycine. The effects of three KC inactivators on IR‐injury after rat liver tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…For this, we examined the ability of dietary glycine to inhibit PCB-induced tumor promotion, since several studies have shown that glycine decreases the production of superoxide and TNF-α by Kupffer cells (Ikejima et al 1996;Rose et al 1999a;Rose et al 1997a;Rusyn et al 1999). The inhibition by glycine of TNF-α production by Kupffer cells is not as strong as using agents such as gadolinium chloride or methyl palmitate, but that may be an advantage for a therapeutic agent (Rentsch et al 2005). Kupffer cell inhibition by glycine has also been shown to affect lipid metabolism in the liver (Neyrinck 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For this, we examined the ability of dietary glycine to inhibit PCB-induced tumor promotion, since several studies have shown that glycine decreases the production of superoxide and TNF-α by Kupffer cells (Ikejima et al 1996;Rose et al 1999a;Rose et al 1997a;Rusyn et al 1999). The inhibition by glycine of TNF-α production by Kupffer cells is not as strong as using agents such as gadolinium chloride or methyl palmitate, but that may be an advantage for a therapeutic agent (Rentsch et al 2005). Kupffer cell inhibition by glycine has also been shown to affect lipid metabolism in the liver (Neyrinck 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental and clinical studies have shown that glycine minimizes reperfusion injury due to organ manipulation during harvest and liver transplantation [18] . In addition, it was shown that glycine modulates Kupffer cell and TNF ␣ activation and prevents apoptosis in a model of cold ischemia [19] . Our findings of reduced TNF ␣ content in liver tissue might favor the assumption that glycine prevents Kupffer cell activation after warm liver ischemia, as described previously in a model of cold ischemia [6] .…”
Section: Discussionmentioning
confidence: 99%
“…KC were blocked upon reperfusion [20,37,38], or when antioxidants were given at various time points during liver transplantation [11,29,39]. This suggests that ROS, either released intracellulary or in the sinusoidal space, might be a target for tacrolimus action [32,40].…”
Section: Discussionmentioning
confidence: 99%